Sketch your stuff : 200 things to draw and how to draw them - Stich, Jon (Kent, [UK] Search Press, [2017] ©2017, 2017)
Want to learn to draw, but stuck for how to get started? 'Sketch Your Stuff' shows you how to turn everyday objects that fill your home into subjects for your sketchbook - allowing you to work on your drawing skills at any moment of the day
1
Keywords: Drawing